83.3k views
1 vote
Average rate of change from G from x=3 to x=4 is

Average rate of change from G from x=3 to x=4 is-example-1
User Hjl
by
5.9k points

1 Answer

4 votes

For a function of
f, the average rate of change can be found as follows:



ARC=(f(x_(2))-f(x_(1)))/(x_(2)-x_(1))


So, we only need two points to compute this value. So, in this problem we have a table with several points, but the problem establishes that the ARC we need to find is the one between two points, that is, when x=3 and x=4. In this problem,
g is the function, so:



ARC=(g(x_(2))-g(x_(1)))/(x_(2)-x_(1))\\ \\ ARC=(9-8)/(4-3) \\ \\ \therefore \boxed{ARC=1}

User Veena
by
6.7k points